A case of recurrent systemic capillary leak syndrome triggered by influenza A infection associated with cardiogenic shock supported by veno-arterial extracorporeal membrane oxygenation. (March 2023) - Ling, Steven Kin-ho; Fong, Natalie Man-chi; Chan, Mandy Sze-man
Systemic capillary leak syndrome (SCLS) is a rare and under-recognized disease which is potentially fatal. We report a case of SCLS triggered by influenza A infection associated with fulminant cardiogenic shock, successfully supported by veno-arterial extracorporeal membrane oxygenation (VA-ECMO). Strong clinical suspicion with appropriate supportive treatment can be life-saving for patients with SCLS.